The Effect of Special Exercises by Using Training Methods to Assist in the Development of Some Motor Abilities and Handstand Skill of Still Rings for Young People (Medico Legal Update, 2020)
Artistic gymnastics is considered as one of the plays that developed, in which the performance reaches to the top, we exactly dedicate to the still rings device that its exercises characterized by strength, stability, pronation and tucks flyaway of handstand, so an athlete needs to strength, speed, endurance, fitness, balance and flexibility. This study aims at preparing some special exercises using assistance tools to improve some motor and skills abilities on the Still Rings device. This study hypothesized that there is no significant differences between pre and post-tests of the experimental and control groups in the motor abilities and handstand skills of still rings device for the good of experimental group. The researchers used descriptive method with two groups. After homogenizing and equaling the sample of the research, the researchers applied special exercises on the experimental group that made up of (24) training modules. The researchers concluded that the special exercises with assistance tools have a great role in improving the motor and skillful abilities of the experimental group. The use of these assistance tools in improving the performance of some skills which assist in saving time and effort of the trainer and the player.